Analisis Tingkat Kematangan (Maturity Level) Tata Kelola Teknologi Sistem Informasi Akademik Menggunakan Cobit 4.1 pada STAIN ParePare - Diah Asdiany; Azaliyatul hidayah (Kontigensi : Jurnal Ilmiah Manajemen, 2018)
This research was conducted with the aim of (1) analyzing the maturity level (Maturity Level) of IT governance in the Academic Information System at the current STAIN Pare-pare; (2) mapping and measuring IT governance in the appropriate Academic Information System to optimize the quality of academic services at STAIN Pare-pare by referring to the COBIT framework standards; (3) analyzing the Academic Information System at STAIN Pare-pare which is integrated with other back-office information systems to suit the vision, mission, and goals of the organization. This study uses primary data and secondary data. In this study, the sample used amounted to five people consisting of elements of leadership who are directly related to or in charge of the academic subdivision and the Head of the TIPD unit. The data was collected through a questionnaire, and a maturity level was calculated based on the Cobit 4.1 framework. The results of this study indicate that: (1) implementing the Maturity Model COBIT 4.1 as a tool for Academic Information System Technology Governance, facilitating documentation, and facilitating the preparation of governance in Academic Information System Technology; (2) know the Maturity Level in STAIN Pare-pare at this time by mapping and measuring the maturity level of the Academic Information System Technology governance; (3) based on the results of mapping and maturity measurements and integrated with other back offices, then the output of Academic Information System Technology Governance is in line with the Vision, Mission, and Objectives of STAIN Pare-pare. It shows that the Maturity Level of Academic Information System Technology Governance in STAIN Pare-pare is at level three (Defined).